Intra-Atrial Dyssynchrony Using Cardiac Magnetic Resonance to Quantify Tissue Remodeling in Patients with Atrial Fibrillation - Ciuffo,Luisa Allen (2019)
Abstract Background: Recent studies suggest that left atrial (LA) late gadolinium enhancement (LGE) can quantify the underlying tissue remodeling that harbors atrial fibrillation (AF). However, quantification of LA-LGE requires labor-intensive magnetic resonance imaging acquisition and postprocessing at experienced centers. LA intra-atrial dyssynchrony assessment is an emerging imaging technique that predicts AF recurrence after catheter ablation. We hypothesized that 1) LA intra-atrial dyssynchrony is associated with LA-LGE in patients with AF and 2) LA intra-atrial dyssynchrony is greater in patients with persistent AF than in those with paroxysmal AF. Method: We conducted a cross-sectional study comparing LA intra-atrial dyssynchrony and LA-LGE in 146 patients with a history of AF (60.0 ± 10.0 years, 30.1% nonparoxysmal AF) who underwent pre-AF ablation cardiac magnetic resonance (CMR) in sinus rhythm. Using tissue-tracking CMR, we measured the LA longitudinal strain in two- and four-chamber views. We defined intra-atrial dyssynchrony as the standard deviation (SD) of the time to peak longitudinal strain (SD-TPS, in %) and the SD of the time to the peak pre-atrial contraction strain corrected by the cycle length (SD-TPSpreA, in %). We used the image intensity ratio (IIR) to quantify LA-LGE. Results: Intra-atrial dyssynchrony analysis took 5 ± 9 minutes per case. Multivariable analysis showed that LA intra-atrial dyssynchrony was independently associated with LA-LGE. In addition, LA intra-atrial dyssynchrony was significantly greater in patients with persistent AF than those with paroxysmal AF. In contrast, there was no significant difference in LA-LGE between patients with persistent and paroxysmal AF. LA intra-atrial dyssynchrony showed excellent reproducibility and its analysis was less time-consuming (5 ± 9 minutes) than the LA-LGE (60 ± 20 minutes). Conclusion: LA Intra-atrial dyssynchrony is a quick and reproducible index that is independently associated with LA-LGE to reflect the underlying tissue remodeling.